EFFECT OF HEALTH EDUCATION OF SAFETY RIDING USING AUDIOVISUAL MEDIA ON KNOWLEDGE, ATTITUDES AND SUBJECTIVE NORMS OF JUNIOR HIGH SCHOOL STUDENTS IN SAMARINDA INDONESIA - Rahman, Wahnadita; Setyowati, Dina Lusiana; Ifroh, Riza Hayati (Public Health of Indonesia, 2019)
Background: Traffic accidents are the main cause of death for adolescents aged 16-19 years. Teenagers in junior high school age are very vulnerable to traffic accidents. The importance of giving safety riding health education to junior high school students is to prepare them in the active phase of riding in an effort to prevent traffic accidents.Objective: To determine the effect of health education about safety riding using audiovisual on the knowledge, attitudes and subjective norms of VII grade students of the Junior High School of 32 Samarinda, Indonesia.Methods: This research employed a quasi-experimental with a non-equivalent pretest-posttest design, with a sample of 40 students in each intervention and control group selected using purposive sampling technique. Data were analyzed using Mann-Whitney test and Independent t-test.Results: There were significant differences in knowledge, attitudes, and subjective norms between the intervention and control groups (p-value = 0.000).Conclusion: The use of audiovisual is effective to provide health education about safety riding on the level of knowledge, attitudes, and subjective norms among junior high school students.